2014
DOI: 10.1111/j.2040-0209.2014.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Who Wants to Farm? Youth Aspirations, Opportunities and Rising Food Prices

Abstract: Summary Who wants to farm? In an era of land grabs and environmental uncertainty, improving smallholder productivity has become a higher priority on the poverty and food security agenda in development, focusing attention on the next generation of farmers. Yet emerging evidence about the material realities and social norms and desires of young people in developing countries indicates a reasonably widespread withdrawal from work on the land as an emerging norm. While de‐agrarianisation is not new, policymakers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 19 publications
5
84
0
3
Order By: Relevance
“…For Tadele and Gella (2012) working in areas of Ethiopia where land scarcity is a problem, the larger issue is that farming and rural life are seen as Bbackward, demanding and even demeaning -especially for those who have gone through years of education with higher hopes and expectations^(p.41). This chimes with the findings of a multi-country study (including five sites in four African countries) reported by Leavy and Hossain (2014). These authors conclude that Bfarming is not a favoured option for the younger generation in rural areas of developing countries, even those in which agriculture remains the mainstay of livelihoods and the rural economy^(p.38).…”
Section: Introductionsupporting
confidence: 78%
“…For Tadele and Gella (2012) working in areas of Ethiopia where land scarcity is a problem, the larger issue is that farming and rural life are seen as Bbackward, demanding and even demeaning -especially for those who have gone through years of education with higher hopes and expectations^(p.41). This chimes with the findings of a multi-country study (including five sites in four African countries) reported by Leavy and Hossain (2014). These authors conclude that Bfarming is not a favoured option for the younger generation in rural areas of developing countries, even those in which agriculture remains the mainstay of livelihoods and the rural economy^(p.38).…”
Section: Introductionsupporting
confidence: 78%
“…While the value of such a shift was questioned by older people in many communities, it was a move that fitted squarely within global norms that gave primacy to economic growth for status and power, and which had ushered in a 'corporate food regime' by which food 'from nowhere' was (and still is) valorised in a process that has included dispossession of small farmers, fisherfolk and pastoralists (McMichael 2009a: 147). We found young people leaving small-scale agriculture in droves (Leavy and Hossain 2014; also see White 2012), some to new work in the towns, others to small local industries including in food sectors such as poultry-raising. Remaining part of production and consumption systems that were neither marketnor profit-oriented was widely painted by people on low incomes as an unimpressive life choice.…”
Section: Right To Workmentioning
confidence: 82%
“…unreliable when it came to income, and badly timed when it came to provisioning (Leavy and Hossain 2014). …”
Section: The Changing Business Of Small-scale Farmingmentioning
confidence: 99%
“…The research focus was thus on an urban context. Much research about education in Ethiopia has been conducted in rural areas, and has particularly focused on the material and cultural barriers to education specific to such contexts (for example Abebe, 2008;Admassie, 2003;Leavy and Hossain, 2014). It was anticipated that many of these barriers might be different or absent in towns and cities.…”
Section: Methodsmentioning
confidence: 99%